Garlic Extract Increased Acrylamide Formation in French Fries Obtained by Different Cooking Methods - Simge Sipahi; Timur Hakan Barak; Özge Can; Betül Zehra Temur; Murat Baş; Duygu Sağlam (Foods, 2024)
Fried potato products are the largest dietary source of acrylamide, a potential carcinogen formed at high temperatures. Previous studies suggested that garlic powder could decrease the development of acrylamide; however, there has not been much focus on the effect of garlic extract. The aim of this study was to investigate the effect of garlic extract exposure on the development of acrylamide in French fries in popular home cooking techniques such as pan-frying, air-frying, and oven-frying. Initially, the antioxidative profile, total phenolic content, and chlorogenic acid content of garlic were analyzed. Subsequently, potatoes were treated with garlic extract and fried using pan-frying, air-frying, and oven-frying techniques. Acrylamide levels were then quantified through HPLC and compared to control groups. The findings showed that garlic exposure increased the acrylamide formation in French fries obtained with air-frying (311.95 ± 0.5 μg/kg) and with oven-frying (270.32 ± 23.4 μg/kg) (p < 0.005 *). This study offers new insights into varying acrylamide formation levels in domestic practices. Unlike previous studies, this study is the first to question the effect of aqueous garlic extract exposure. Further research is required to comprehend the interaction between garlic exposure and acrylamide formation in household settings.